Chagas' heart disease: gender differences in myocardial damage assessed by cardiovascular magnetic resonance. Issue 1 (January 2017) - Assunção, Antonildes; Jerosch-Herold, Michael; Melo, Rodrigo; Mauricio, Alejandra; Rocha, Liliane; Torreão, Jorge; Fernandes, Fabio; Ianni, Barbara; Mady, Charles; Ramires, José; Kalil-Filho, Roberto; Rochitte, Carlos
Abstract Background Since a male-related higher cardiovascular morbidity and mortality in patients with Chagas' heart disease has been reported, we aimed to investigate gender differences in myocardial damage assessed by cardiovascular magnetic resonance (CMR). Methods and results Retrospectively, 62 seropositive Chagas' heart disease patients referred to CMR (1.5 T) and with low probability of having significant coronary artery disease were included in this analysis. Amongst both sexes, there was a strong negative correlation between LV ejection fraction and myocardial fibrosis (maler  = 0.64, femaler  = 0.73, bothP  < 0.001), with males showing significantly greater myocardial fibrosis (P  = 0.002) and lower LV ejection fraction (P  < 0.001) than females. After adjustment for potential confounders, gender remained associated with myocardial dysfunction, and 53% of the effect was mediated by myocardial fibrosis (P for mediation = 0.004). Also, the transmural pattern was more prevalent among male patients (23.7 vs. 9.9%, P  < 0.001) as well as the myocardial heterogeneity or gray zone (2.2 vs. 1.3 g, P  = 0.003). Conclusions We observed gender-related differences in myocardial damage assessed by CMR in patients with Chagas' heart disease. As myocardial fibrosis and myocardial dysfunction are associated to cardiovascular outcomes, our findings might help to understand the poorer prognosis observed in males in Chagas' disease.